SERBIAN ECONOMY IN TRANSITIONAL, EUROPEAN AND WORLD ECONOMIC CRISIS - Ivana Bozic Miljkovic (European Scientific Journal, ESJ, 2013)
At the transition beginning, economic crisis in Serbia was caused by political crisis in the area of former SFRY and institution crisis which, at the time were not ready for changing of the milieu they developed in until then. Political and economic crisis which started at that time in the area of former Yugoslavia, was intensified by the new transition crisis which have, in Serbia, being present – more or less intensively, until present days. Events in politics during the nineties, the introduction of economic sanctions by international organizations, hyperinflation, unemployment increase and overflow of gray economy, additionally contributed the crisis to last longer that it is usual for transition process. The economic crisis went on during the first decade of the new century. This period is known by accelerated privatization which, from the point of the crisis was double-edged sword: on one side, great inflow of assets partially preserved “social peace” and the crisis felt less; on the other, insufficient investments in production and long lists of redundancy workers from newly privatized companies anticipated that the economic crisis in the future will be wider and become the crisis of the social system. The great world economic crisis, which in 2008. started in the USA, had consequences for the whole world. Though, Serbia geographically and economically was not on the front line of the direct impact countries, yet economic consequences were great because the crisis hit the vulnerable system which in the previous decades was already in the crisis. Slowing of economic development and transition reforms, are most obvious consequences of its effect in Serbia. Decades of Serbian crisis and the possibility of having “Greek script” in Serbia, motivated the present government to adopt a new package of measures to ease the crisis, which will be effective in near future.